A multi-scale approach interpreting sediment processes and distribution from desert sand colour in central Saudi Arabia - Bradley, Andrew V.; McLaren, Sue J.; Al-Dughairi, Ahmed; Khalaf, Nadia R. (Wiley, 2018)
In central Saudi Arabia the redness of sands observed on satellite imagery, often related to iron oxide amount, was used to better interpret geomorphic processes operating in the area. To compare variations between dune and interdune morphology, linear and dome dunes, and an ephemeral river partly buried under the sand sea, Nafud Al-Thuwayrat, a multiscale approach was used to identify the spatial variation in causes of iron oxide amounts and colour. Macro-scale mapping of Image Spectral Redness identified that the extent and intensity of colour grading across the orientation of well-defined linear and dome dune types, interdunes and the Wadi Al-Rimah, indicated sediment mixing of different provenance. Meso-scale chemical, physical and colour analysis of surface samples indicated that iron oxide coated grains were present within all the samples and was not the sole control on Image Spectral Redness. The reddest sediments were the best sorted medium-to fine-quartz sands with iron oxide bearing chemistry and the paler sediments contained coarser sands with additional feldspars, calcite and gypsum. Micro-scale analysis of grain characteristics found dune-interdune contrasts and that the reddest sands with iron coatings were of aeolian origin and the paler sands contained larger fluvial material mixed with reworked aeolian deposits. Dust in the area consists of high amounts of iron oxide and appears to be a major contributor to redness in the sand dunes. These controls on colour show the sand seas are paler westwards because a major river, and local drainage systems, deliver fluvial sediments from the carbonate and sandstone bedrock into the quartz rich aeolian material from the linear dunes. Evaporite deposits dominate in the paler interdunes, and south of the Wadi the dome dunes are the reddest as they are not migrating but building up. This multiscale approach has provided a modern analogy of processes for palaeoenvironmental studies.